Features of the creation the promotional video industrial company by means of computer graphics - Savchenko, L.; Vorontsova, D.; Krukovsky В. (Theory and practice of design, 2015)
Based on the developed scenario promo video manufacturing company in the production and installation of steel structures are considered particularly the creation of three-dimensional objects for five scenes, their subsequent animation and visual effects modeling software environment MAXON CINEMA 4D.